China's strategic interests in the South China Sea power and resources - Burgos Caceres, Sigfrido (Routledge/Taylor & Francis Group, 2014)
"Explores China's strategic interests in the South China Sea, with a specific emphasis on power projection and resource security. Contains sections on China's power and resources and case studies on Japan, Vietnam, the USA and the Philippines, and discusses how China's actions are reshaping the power dynamics in East and South-East Asia"-- Provided by publisher.